2013
DOI: 10.1107/s1600536813001207
|View full text |Cite
|
Sign up to set email alerts
|

Orphenadrinium dihydrogen citrate

Abstract: In the title salt, C18H24NO+·C6H7O7 −, the dihedral angle between the benzene rings in the cation is 74.2 (5)°. In the crystal, anion–anion O—H⋯O hydrogen bonds and weak O—H⋯O inter­actions form infinite chains along [100]. Between these chains, cation–anion N—H—O hydrogen bonds are observed, forming an alternate pattern of cation and anion layers and leading to a two-dimensional network parallel to (100).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A study on carbinoxamine maleate describing the crystallographic structure and chemical relationships of Clistin to other well known antihistaminic drugs and also correlating these chemical aspects with the pharmacological effects produced by this new drug as compared with other antihistaminic agents has been reported by Bertolasi et al (1980). Some number of related structures was reported earlier -orphenadrinium picrate picric acid (Fun et al, 2010); orphenadrinium dihydrogen citrate (Kaur et al, 2013); doxylamine hydrogen succinate (Parvez et al, 2001). In view of the importance of carbinoxamine, this paper reports the crystal structure of the title compound, (I).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…A study on carbinoxamine maleate describing the crystallographic structure and chemical relationships of Clistin to other well known antihistaminic drugs and also correlating these chemical aspects with the pharmacological effects produced by this new drug as compared with other antihistaminic agents has been reported by Bertolasi et al (1980). Some number of related structures was reported earlier -orphenadrinium picrate picric acid (Fun et al, 2010); orphenadrinium dihydrogen citrate (Kaur et al, 2013); doxylamine hydrogen succinate (Parvez et al, 2001). In view of the importance of carbinoxamine, this paper reports the crystal structure of the title compound, (I).…”
Section: Methodsmentioning
confidence: 95%
“…For the effect of antihistamines on psychomotor performance, see: Seppala et al (1981). For related structures, see: Bertolasi et al (1980); Parvez et al (2001); Fun et al (2010); Kaur et al (2013). For standard bond lengths, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…Drug design and research in vibrational spectroscopy rely heavily on quantum chemical computations and molecular modeling [21,22]. The XRD study of the ODC is reported by Kaur et al [23]. The quantum chemistry theory, DFT, molecular models and vibrational spectroscopy are heavily used in drug research and development [24].…”
Section: Introductionmentioning
confidence: 99%
“…Docking together with MD simulations was used to determine the biological activity of ODC by determining drug likeness, ligand interactions and appropriate protein interactions. Methods ODC was obtained as a gift sample from Kaur et al [23] and the vibrational spectra are given in Fig. S1 and Fig.…”
Section: Introductionmentioning
confidence: 99%